Thermal properties and reliability of eutectic mixture of stearic acid-acetamide as phase change material for latent heat storage. (March 2017) - Ma, Guixiang; Han, Lipeng; Sun, Jinhe; Jia, Yongzhong
Highlights: The system of stearic acid-acetamide binary mixtures were studied as phase change material. The eutectic mixtures featured low melting temperatures and high latent heats of fusion for latent heat storage. Solid-liquid phase diagrams for the system were constructed. Negligible change in stability after 500 heating/cooling cycles. Abstract: The thermal properties and reliability of the stearic acid (SA) with acetamide (AC) binary mixture were characterized using differential scanning calorimetry (DSC), powder X-ray diffraction (XRD), thermogravimetric analysis (TG) and Fourier transform infrared spectroscopy (FT-IR). The phase diagrams for the SA-AC binary mixture with AC in the metastable and the stable form were constructed. The eutectic system with stable AC is 0.604 mol fraction SA, and displayed a melting temperature ( T m ) of 64.55 °C and latent heat of melting (Δ H m ) of 193.87 J·g −1 . The eutectic systems with metastable AC are 0.397 and 0.604 mol fraction SA. The melting temperatures are 62.23 °C and 62.54 °C, and latent heats of fusion are 222.10 J·g −1 and 194.28 J·g −1, respectively. Following accelerated thermal cycling tests, TG and FT-IR analysis indicate that the eutectic mixture (χSA = 0.397) with the metastable AC has good cyclic and thermal stability. The results show that the SA-AC eutectic mixture use as phase change material (PCM) possess good prospect for low temperature thermal energy storage (TES) applications.